Microbial chassis development for natural product biosynthesis - Xu,X; Liu,Y; Du,G; Ledesma-Amaro,R; Liu,L (Trends in Biotechnology, 2020)
Engineering microbial cells to efficiently synthesize high-value-added natural products has received increasing attention in recent years. In this review, we describe the pipeline to build chassis cells for natural product production. First, we discuss recently developed genome mining strategies for identifying and designing biosynthetic modules and compare the characteristics of different host microbes. Then, we summarize state-of-the-art systems metabolic engineering tools for reconstructing and fine-tuning biosynthetic pathways and transport mechanisms. Finally, we discuss the future prospects of building next-generation chassis cells for the production of natural products. This review provides theoretical guidance for the rational design and construction of microbial strains to produce natural products.